(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Service activities carried out by STKIP Muhammadiyah Kuningan students on a training basis provide space for students to develop the soft skills and hard skills they have. This community service program was carried out at Eakkapapsasanawich Islamic School Krabi Thailand with the aim of developing students’ talent interests in the field of public speaking and Islamic arts. This service method is carried out in a group discussion forum (FGD) between teachers, boarding school administrators, students, and KKN students. In addition to using training methods and providing assistance as a follow-up to the training. The result of this service activity is that students are able to develop their interests and talents in the field of public speaking and Islamic arts, with the material and training provided.